PH-Sensitive self-assembling nanoparticles for tumor near-infrared fluorescence imaging and chemo–photodynamic combination therapy. Issue 1 (26th November 2015) - Hou, Wenxiu; Zhao, Xin; Qian, Xiaoqing; Pan, Fei; Zhang, Chunlei; Yang, Yuming; de la Fuente, Jesús Martínez; Cui, Daxiang
Abstract : pH-Sensitive self-assembling anti-tumor prodrug nanoparticles for the diagnosis and chemo-photodynamic combination treatment of tumor. Abstract : The development of visual tumor theranostic nanoparticles has become a great challenge. In this study, d -α-tocopheryl polyethylene glycol 1000 succinate (TPGS) was conjugated to acid-sensitive cis -aconitic anhydride-modified doxorubicin (CAD) to obtain pH-sensitive anti-tumor prodrug nanoparticles (TCAD NPs) via self-assembling. Subsequently, the photosensitizer chlorin e6 (Ce6) was loaded into the resulting prodrug nanoparticles to prepare a novel tumor near-infrared fluorescence imaging and chemo–photodynamic combination therapy system (TCAD@Ce6 NPs). An accelerated release of doxorubicin (DOX) and chlorin e6 (Ce6) from the TCAD@Ce6 NPs could be achieved due to the hydrolysis of the acid-sensitive amide linker under mild acidic conditions (pH = 5.5). An in vitro experiment showed that A549 lung cancer cells exhibited a significantly higher uptake of DOX and Ce6 by using our delivery system than the free form of DOX and Ce6. An in vivo experiment showed that TCAD@Ce6 NPs displayed better tumor targeting gathering through the enhanced permeability and retention (EPR) effect than free Ce6, thus improving fluorescence imaging. Moreover, the chemo–photodynamic combination therapy of TCAD@Ce6 NPs combined with near-infrared laser irradiation was confirmed to be capable of inducing high apoptosis and necrosis of tumor cells (A549) in vitro and to display a significantly higher tumor growth suppression in the A549 lung cancer-bearing mice model. Furthermore, compared with exclusive chemotreatment (DOX) or photodynamic treatment (Ce6), our system showed enhanced therapeutic effects both in vitro and in vivo . In conclusion, the high performance TCAD@Ce6 NPs can be used as a promising NIR fluorescence imaging and highly effective chemo–photodynamic system for theranostics of lung cancer, etc. in the near future.